IMPROVING STUDENTSâ ACHIEVEMENT IN SPEAKING BY USING PICTURE - Rambe, Marina Sari (LP2M Universitas Muslim Nusantara Al Washliyah, 2017)
Learning Language as well as learning English is also the implementation of searching knowledge. The goals in language learning is the students are able to speak English well and use English as their language to communicate with another people in daily life. In language learning, speaking is one of the important things to have, but the students are not able to speak up in English class. Using media is one of the way that can improve the students achievement in speaking class. The researcher will be focus to use picture as media in this research. The researcher formulate there is an improvement of students achievement in speaking by using picture as the problem in this research. The researcher use Classroom Action Research (CAR) Method to analyze the data in this research. The researcher take the first year students of MTS N 2 Medan as the population and 30 students as sample where the researcher get the sample by random. The research take 2cycle in this research. The instrument to applied to collect the data was speaking test. Besides that, the writer also used interview, observation sheet and diary note to identify what happened in the classroom. After analyzed the data, it was obtained that means increased from the Test-1 in cycle I 71,73% until test-3 in cycle II 83,40 % and the total score increased 90.0% . So, the use of picture improve studentsâ speaking achievement.